Influence of Cash Holding and Dividend Against Firm Value on Property Company and Real Estate Listed on the Indonesia Stock Exchange - Siti Rosa Lismawati; Candra Hadi Utomo; Fenty Fauziah (International Journal of Quantitative Research and Modeling, 2022)
The purpose of this study was to determine and analyze the effect of cash holding and dividends on firm value in property and real estate companies listed on the Indonesia Stock Exchange, either partially or simultaneously. The quantitative type of research used in this study, the research population is all property and real estate companies listed on the Indonesia Stock Exchange for the 2010-2019 period and the sample selection technique uses purposive sampling so that a sample of companies is obtained. The data collection techniques with documentation and are secondary data used in research. The data analysis technique used is panel data with the help of a statistical data processing program called Eviews 9. The results of the study, cash holding partially has a negative and insignificant effect on firm value, while dividends partially have a positive and significant effect on firm value, while simultaneously cash holding and dividends have a significant effect on firm value.